DESERT RATS - Unknown, Author (Scientia Militaria - South African Journal of Military Studies, 2012)
An hour to spare this pen and me A word I'll pen whilst thoughts are free To write, and pay those "Rats" their due As we know them, me and you. Hard and lean, covered in sand Fast and sure. Gad! what a band, That dirty but efficient lot And "Desert Rats" that name they've got.